Regional Cooperation in Supporting Increasing Competitiveness and The Regional Economy Through Tourism - Agnes Wirdayanti; Sussy Novita Sari (Iapa Proceedings Conference, 2022)
Cooperation between regions in tourism development is inseparable from sectoral ego problems, so an analysis is carried out using the 5 elements of Wright's IGR. This study aims to determine the inter-regional cooperation in the development of tourism and determine the driving and inhibiting factors. The research method uses descriptive qualitative. The data used are primary and secondary data. Data collection techniques using interviews and documentation. Data analysis using interactive model. The results of the study explain that there is a division of roles between the parties involved in the collaboration. Interactions between public officials appear to be similar in aspects of behavior, beliefs, perceptions and preferences. Continuous communication that is established on a regular basis. Executive and legislative officials also play a role in the implementation of cooperation and there is clarity on the role of the appointed administrator. Meanwhile, in the policy focus, the capacity of the budget to implement cooperation comes from each party and the central government's policies are followed up by local governments. The driving factors for cooperation are the similarity of ideas, the economic benefits and the support of regional leaders. The inhibiting factor is limited funds. This research has implications for the addition of the role of local government as a dynamist, the use of village fund allocations for villages for tourism development programs and the local government together with the community better utilize the cultural potential.